ENVIRONMENTAL AWARENESS: AN EMPIRICAL STUDY ON SHOES THRIFT IN INDONESIA - Ahmad Wajih Wastiq Wajdie; Wira Bharata (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Green environmental activities play an important role in influencing individual consumer behaviour to produce purchase intentions on a product This study implements the impact of Environmental Awareness in the thrifting business to measure the influence of Purchase Intention using Brand Awareness, Promotional Effort in Social Media, and Perceived Value conducted on Uncharted social media followers. This type of research is quantitative using associative methods and the number of respondents is 110 collected through online surveys using Google Form. Testing was carried out using the Structural Equational Model (SEM). The research findings prove that Brand Awareness has a positive effect on Perceived Value and Purchase Intention, Promotional Effort in Social Media has a positive effect on Perceived Value and Purchase Intention, and Perceived Value has a positive effect on Purchase Intention. In addition, Perceived Value can mediate the relationship of both Brand Awareness and Promotional Effort in Social Media to Purchase Intention.